2011
DOI: 10.5539/ass.v7n6p184
|View full text |Cite
|
Sign up to set email alerts
|

Class Size and Academic Achievement of Secondary School in Ekiti State, Nigeria

Abstract: The study looked at the class size as it relates to academic performance of students in Ekiti state of Nigeria between 1990 and 1997. The study population was the results of the West African School Certificate Examinations (WASCE) conducted between 1990 and 1997 in 50 secondary schools in both rural and urban areas of the state. One validated instrument Students' Class Size Questionnaire (SCSQ) was used for data collection. One hypothesis was formulated and answered. Data were analysed using mean and t -test. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The study concluded that improvement in the tasks of instructional resource inputs, curriculum delivery, and students' learning requires effective and goal-oriented interrelationship between the school and other stakeholders in education. Joseph & Philias (2011) looked at the class size as it relates to the academic performance of students in the Ekiti State of Nigeria between 1990 and 1997. The study population was the results of the West African School Certificate Examinations (WASCE) conducted between 1990 and 1997 in 50 secondary schools in both rural and urban areas of the state.…”
Section: Runasmentioning
confidence: 99%
“…The study concluded that improvement in the tasks of instructional resource inputs, curriculum delivery, and students' learning requires effective and goal-oriented interrelationship between the school and other stakeholders in education. Joseph & Philias (2011) looked at the class size as it relates to the academic performance of students in the Ekiti State of Nigeria between 1990 and 1997. The study population was the results of the West African School Certificate Examinations (WASCE) conducted between 1990 and 1997 in 50 secondary schools in both rural and urban areas of the state.…”
Section: Runasmentioning
confidence: 99%